Note on Self-Restraint as an Online Entry-Deterrence Strategy - Liu, Yunchuan; Gupta, Sunil; Zhang, Z. John (Management Science, 2006)
We develop a game-theoretical model to show that in the markets where price consistency across channels is critical, an incumbent brick-and-mortar retailer can deter the online entry of a pure-play e-tailer by strategically refraining from entering online. In the markets where price consistency is not a constraint, we find that the incumbent can deter the e-tailer’s entry only if it enters online and credibly operates the online channel as an independent profit center. In other words, the incumbent must be willing to cannibalize its own brick-and-mortar business by charging a low online price. We also discuss some social welfare implications of retail online entry and the managerial insights of our analysis.